DEVELOPMENT OF TOOLS FOR CONDUCTING PRACTICAL AND LABORATORY LESSONS WITH ROBOTIC DEVICES IN DISTANCE EDUCATION CONDITIONS - Михайлов, Євген; Лінгур, Валерій; Борисов, Владислав; Панфіленко, Олег; Махновський, Кирило (SWorldJournal, 2023)
The analysis of existing tools for designing and modeling robotic devices has been conducted, revealing that the most suitable platform for conducting remote sessions in exploring various robotic devices is the virtual experimentation platform for robots,